Web based information model to support maintenance and operations management. - Zahrizan, Zakaria (2007)
Facilities Management (FM) has been considered as facilities maintenance and operation and has a broad range of functions. Because of its nature, information can be lost during maintenance operations and it will affect decision making. Information Technology (IT) may be used as a tool to make an effective decision- making and productivity of the organisation can be further improved through the use of IT. Therefore the used of a Computerised Maintenance Management System (CMMS) as an operational and maintenance management tool can be used. The purpose of a CMMS is to manage, capture, and track inspection, maintenance and repair activities of an organisation, because in a world of increasing information flows, data retrieval becomes more and more important. Therefore, the purpose of this study is to identify the requirement of electronic management for the maintenance department to support their maintenance operations. This research is also aimed to develop and gauge the effectiveness of the proposed framework for an information model called electronic Maintenance Online System (eMOST) to support maintenance and operations at the Office of Development and Asset Management or Pejabat Pembangunan dan Pengurusan Harta (PPPH), Kolej Universiti Kejuruteraan dan Teknologi Malaysia (KUKTEM) as a facility management tool. In this research, Cold Fusion Markup Language and MS Access as a database were used to develop the proposed information model. It starts with developing the process model using IDEFØ notation before transform it into programming language.. Prior to the development of eMOST, quantitative studies had been conducted by using three different sets of questionnaires which were designed to meet the objectives of the study. The first set of questionnaire tackled the issues of maintenance management at higher institutions in Malaysia and the second set of questionnaire is to investigate the customer satisfaction index on the performance of maintenance activities done by PPPH, KUKTEM. The third questionnaire was meant to evaluate the proposed information model i.e eMOST from users’ perspective and perceptions. The results from analysis of the survey data showed that, none of the higher learning institutions in Malaysia used any facility management software or CMMS to assist their maintenance activities as the majority of them were using out-sourcing method to carry out their maintenance activities and therefore the use of eMOST has expedited the response time taken by PPPH.